Faktor Orangtua Pada Adiksi Internet Remaja: Systematic Literature Review - Pranata, Dwi Chandra; Nurul Hartini; Fairuzzaman, Reyhan (IDEA: Jurnal Psikologi, 2025)
Internet addiction in adolescents is something that should happen among life in the digital era. It is a consequence where the internet and digital devices are the basic needs of people today. Although adolescence is a risky stage of development, adolescents must also have strong internal factors in regulating or controlling themselves in preventing internet addiction. In addition, one of the most important external factors in adolescent internet addiction is parents. Parents are of course the closest environment or microsystem in adolescents. Adolescents will shape or form from their parents' environment. This study aims to examine the parental factors that influence internet addiction in adolescents. This research method uses systematic literature review and analyzed using PRISMA. Only 10 articles out of 280 literatures were selected. The literature was searched using reputable journal data networks and using related keywords. The results showed that there were differences in sample characteristics, socio-demographic circumstances of parents or children, and methods used. This literature review found that factors related to internal factors within adolescents and parents. These internal factors include self-regulation and habitual behavior by parents. The main factors found were that family and parents can explain the high-low level of internet addiction in adolescents. Family factors include parenting style, parent-child relationship, and parental mediation style. This study shows that the main factors that give clear significance to adolescents' internet addiction are adolescents' intrapersonal factors and their relationship with their parents. In conclusion, parents have an important role in regulating the level of internet addiction.